Deviations in kilometres travelled: The impact of different mobility futures on energy use and climate policy - Thomas Longden (Fondazione Eni Enrico Mattei (FEEM), 2012)
The importance of a focus on mobility and the kilometres travelled using light duty vehicles is reflected in the persistence of strong demand for personal mobility and emissions that tend to be linked with population and economic growth. Simulation results using the WITCH model show that changes in the kilometres driven per year using light duty vehicles have a notable impact on investments in alternate transport options. As a result, different mobility futures have notably different optimal vehicle fleet compositions. As climate policy becomes more stringent, achieving abatement with increased mobility implies large investments in battery related technologies and less investments in technologies related to the conversion of biofuel from biomass. Climate policy consistent with a 2êC temperature increase above pre-industrial levels in 2100 leads to a quick transition to plug-in hybrid drive vehicles. Without decreases in mobility trends the cost effective achievement of such a target results in the electrification of passenger vehicles commencing between 2020 and 2035.
Keywords: Q54; R41; O3; 330; Light Duty Vehicles; Transportation; Mobility; Climate Change Policy; Electric Drive Vehicles; Research and Development